Deutsche Kunst und Dekoration : illustrierte Monatshefte für moderne Malerei, Plastik, Architektur, Wohnungskunst und künstlerische Frauen-Arbeiten - Koch, Alexander (Darmstadt : Alexander Koch, 1897)
From October 1897 onwards the editor Alexander Koch from Darmstadt published, with the Deutsche Kunst und Dekoration, a magazine that became the voice of the new aims and self-confidence of the decorative art by the Art Nouveau movement. Through competition announcements published in the magazine motivation and impulses were given to the entire field of applied arts.The textual contributions published basic information on single artists, on questions regarding architecture and interior decoration but also on artistic techniques, on artists training and on exhibitions in Germany and abroad. Especially the illustrations of the magazine are of particular importance.Alongside numerous illustrations covering all thematic fields there are multicoloured supplements and designs of handcrafts by noted artists of the time (amongst them Hans Thoma, Max Klinger, Herman Obrist, Henry van de Velde). From 1905 onwards issues on the Wiener Werkstätte were regularly published. Since 1932 the Deutsche Kunst und Dekoration was identical in content with the magazine Die Kunst until they merged.(uit: https://www.ub.uniheidelberg.de/Englisch/helios/fachinfo/www/kunst/digilit/artjournals/dk_deko.html)
Online: https://www.ub.uni-heidelberg.de/helios/fachinfo/www/kunst/digilit/artjournals/dk_deko.html
DigiZeitschriften: http://www.digizeitschriften.de/dms/toc/?PPN=urn%3Anbn%3Ade%3Absz%3A16-diglit-63833
Duits
Tijdschriften